bell hooks and transgression through presence: concerns mobilized in pandemic traffic - Scorsolini-Comin, Fabio (2023)
The aim of this critical essay is to problematize the question of the presence category addressed as one of the essential conditions of liberating education in the proposal of the African-American writer bell hooks (1952-2021), having as a reference scenario the non-presential education developed in the pandemic traffic. The proposal of liberating education will be addressed in view of the need to reflect on the pandemic intercourse, and two elements emphasized in the author’s work will be analyzed in depth: voice and body. Based on the example of online reflection groups conducted with nursing students, a pedagogical strategy capable of recognizing and valuing the voice of different actors in the educational process is presented, prioritizing the meeting beyond the presence traditionally defended in training spaces: an encounter that waits, resists and fights for the possibility of genuine presence.